Investigating starch from transgenic potato plants lacking starch branching enzyme I and/or glucan, water dikinase 1 - Gouws, Nina Ellen (Stellenbosch : Stellenbosch University, 2024)
Thesis (MScAgric)--Stellenbosch University, 2024.